Where you live, what you do: depression differences among diverse Chinese nongmin through cognitive openness - Li He; Jiangyin Wang; Yang Yang; Zhilu Tian; Liu Jiang (Frontiers in Psychiatry)
ObjectiveThis study aims to investigate the depression levels among Workers with Agricultural Hukou (WAH) in China, considering their varied living environments, types of work, and social discrimination experiences. It specifically addresses the research question: Is there a significant discrepancy in depression levels among different subgroups within WAH?MethodsThe study utilizes data from the China Family Panel Studies (CFPS) for the years 2018 and 2020. To estimate the depression levels and their variances across different WAH subgroups, we employed three analytical methods: Ordinary Least Squares, Propensity Score Matching, and Two-Stage Least Squares.ResultsOur findings indicate that all WAH subgroups experience higher levels of depression compared to Workers with Non-Agricultural Hukou (WNAH). Among the WAH subgroups, the depression levels, in ascending order, are observed in Rural-to-Urban Migrant Workers (RUMW), Rural Non-Agricultural Workers (RNAW), Subsistence Farmers, and Agricultural Laborers. Notably, these differences in depression levels may be influenced by the mechanism of cognitive openness.ConclusionThe study concludes that there are significant disparities in depression levels among WAH subgroups. Understanding these differences is crucial for targeted mental health interventions and for addressing the broader implications of social discrimination and work-related stress among agricultural workers in China.